2,6-Dihydroxybenzaldehyde Analogues of the Iron Chelator Salicylaldehyde Isonicotinoyl Hydrazone: Increased Hydrolytic Stability and Cytoprotective Activity against Oxidative Stress - Jansová, Hana; Kubeš, Jan; Reimerová, Petra; Štěrbová-Kovaříková, Petra; Roh, Jaroslav; Šimůnek, Tomáš (Chemical research in toxicology, 2018)
Salicylaldehyde isonicotinoyl hydrazone (SIH) is a small molecule and lipophilic chelating agent that firmly binds ferric ions from the cellular labile iron pool and is able to protect various tissues against oxidative damage. Previously, SIH possessed the best ratio of cytoprotective efficiency to toxicity among various iron chelators, including the desferrioxamine, deferiprone, and deferasirox used in clinical practice. Here, we prepared a series of 2,6-dihydroxybenzaldehyde aroylhydrazones as SIH analogues with an additional hydroxyl group that can be involved in the chelation of metal ions. Compound JK-31 (2,6-dihydroxybenzaldehyde 4-chlorobenzohydrazone) showed the best cytoprotective efficiency among the studied compounds including SIH. This compound significantly protected H9c2 cardiomyoblast cells against oxidative stress induced by various pro-oxidants, such as hydrogen peroxide, tert-butyl hydroperoxide, paraquat, epinephrine, N-acetyl- p-benzoquinone imine (a toxic metabolite of paracetamol), and 6-hydroxydopamine. The exceptional cytoprotective activity of JK-31 was confirmed using epifluorescence microscopy, where JK-31-treated H9c2 cells maintained a higher mitochondrial inner membrane potential in the presence of a lethal dose of hydrogen peroxide than was observed with cells treated with SIH. Hence, this study demonstrates the deleterious role of free iron ions in oxidative injury and the potential of 2,6-dihydroxybenzaldehyde aroylhydrazones in the prevention of various types of cardiac injuries, highlighting the need for further investigations into these compounds.
Keywords: Cell Survival; Oxidative Stress; Hydrolysis; chelátory železa; oxidační stres; Drug Stability; Humans; ochranné látky; hydrolýza; kardiomyocyty; Iron Chelating Agents; hydrazony; Benzaldehydes; krysa rodu Rattus; Membrane Potential, Mitochondrial; lidé; zvířata; proliferace buněk; Myocytes, Cardiac; buněčné linie; Cell Line; Protective Agents; Hydrazones; benzaldehydy; Cell Proliferation; Rats; stabilita léku; aldehydy; Animals; membránový potenciál mitochondrií; Aldehydes; viabilita buněk